Molecular breath analysis supports altered amino acid metabolism in idiopathic pulmonary fibrosis - Gaugg, Martin Thomas; Engler, Anna; Bregy, Lukas; Nussbaumer‐Ochsner, Yvonne; Eiffert, Lara; Bruderer, Tobias; Zenobi, Renato; Sinues, Pablo; Kohler, Malcolm (Respirology (Carlton, Vic.), 2019)
ABSTRACT Background and objective Diagnosis of idiopathic pulmonary fibrosis (IPF) is complex and its pathogenesis is poorly understood. Recent findings indicate elevated levels of proline and other amino acids in lung tissue of IPF patients which may also be of diagnostic value. Following these findings, we hypothesized that such altered metabolic profiles would be mirrored in exhaled breath and could therefore be captured non‐invasively in real time. Methods We aimed to validate these results using real‐time exhaled breath analysis by secondary electrospray ionization‐mass spectrometry, which can provide a non‐invasive, painless and fast insight into the metabolism. Breath analysis was performed in a matched 1:1 case–control study involving 21 patients with IPF and 21 control subjects. Results We found significantly (P < 0.05) elevated levels of proline, 4‐hydroxyproline, alanine, valine, leucine/isoleucine and allysine in breath of IPF patients, whereas pyroglutamic acid and phenylalanine did not show significant differences. This coincides with the amino acid's abundance in pulmonary tissue indicating that our observations reflect progressing fibrosis. In addition, amino acid levels correlated across subjects, further supporting a common underlying pathway. We were able to obtain a cross‐validated area under the curve of 0.86, suggesting that these increased amino acid levels in exhaled breath have the potential to be used as biomarkers for IPF. Conclusion We could validate previous findings of elevated lung tissue amino acid levels in IPF and show that online breath analysis might be a practical tool for a rapid screening for IPF. Collagen‐related amino acids are significantly increased in exhaled breath of idiopathic pulmonary fibrosis (IPF) patients compared with healthy controls. The detection of these amino acids using real‐time breath analysis results in a good discrimination between the groups, indicating the possibility for a rapid, non‐invasive screening for IPF. See related Editorial